Sriwijaya University Students' Perceptions of Using English Subtitles in Multimedia Tools for Vocabulary Enhancement - Salsabila, Amira Dellani; Fiftinova, Fiftinova (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study was conducted to find out students’ perceptions of using English subtitles in multimedia tools for vocabulary enhancement, as well as the challenges they face and the strategies they employ to overcome them. A descriptive qualitative research method was used, with 10 students from English and 10 from Indonesian Language Education Study Program at Sriwijaya University as the participants. The data of this study were collected through semi-structured interviews. The data analysis process included data reduction, data display, verification, conclusion drawing, and triangulation through member checking to ensure the credibility of the findings. The findings revealed that students had positive perceptions of using English subtitles, recognizing the significant benefits for vocabulary enhancement. They reported that subtitles helped them connecting spoken and written words, understanding context more easily, identifying new vocabulary in an engaging way, and improving pronunciation. However, students also encountered several challenges when using English subtitles in multimedia tools, such as fast-paced subtitles, unfamiliar or advanced words, mismatched dialogue, and some distractions from subtitles. Furthermore, students also faced technical difficulties, such as unstable internet connections. To overcome these challenges, students employed various strategies, including pausing and replaying videos, slowing down playback speed, and using online dictionaries to look up unfamiliar words.